Review of risperidone for the treatment of pediatric and adolescent bipolar disorder and schizophrenia - Jeffrey R Bishop (Dove Medical Press, 2008)
Jeffrey R Bishop1,2, Mani N Pavuluri21Department of Pharmacy Practice, University of Illinois at Chicago College of Pharmacy, Chicago, IL, USA; 2Department of Psychiatry, Pediatric Mood Disorders Program and Center for Cognitive Medicine, University of Illinois at Chicago College of Medicine, Chicago, IL, USAAbstract: Risperidone is a commonly used medication for the treatment of bipolar disorder and schizophrenia in children and adolescents. It has been studied as a monotherapy treatment in early onset schizophrenia and as both monotherapy and combination therapy for pediatric bipolar disorder. Studies to date indicate that risperidone is an effective treatment for positive and negative symptoms of schizophrenia and mania symptoms of bipolar disorder. In young patient populations, side effects such as weight gain, extrapyramidal side effects, and prolactin elevation require consideration when evaluating the risk benefit ratio for individual patients. Here we review published studies of risperidone for the treatment of bipolar disorder and schizophrenia in children and adolescents to provide practitioners with an overview of published data on the efficacy and safety of risperidone in these patient populations.Keywords: risperidone, bipolar disorder, schizophrenia, children, adolescents